Організаційно-методологічні аспекти оцінки соціальної відповідальності бізнесу - Коноваленко, Анастасія Сергіївна; Коноваленко, Анастасия Сергеевна; Konovalenko, Anastasiia (My University, 2009)
UK: Рассмотрена роль социальной ответственности бизнеса в процессе формирования социальной политики и развития общества. Проведен анализ особенностей взаимодействия бизнес-структур с заинтересованными лицами и государством. Обоснованы основные принципы оценки уровня социальной ответственности бизнеса. EN: Role of social responsibility of business in the process of social policy formation and society development is considered. Analysis of specific interactions between business- structures and stakeholders and state was made. Main principles used for estimating the level of social responsibility of business are grounded.
Keywords: соціальна відповідальність бізнеса; бізнес-структури; стейкхолдери; громада